THE ROLE OF POLITICAL DEVELOPMENT IN REPUBLIC OF SOUTH SUDAN - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Political development has been defined in many ways that reflect the passage of societies' and analysts' preoccupations. One formulation dwell on the emergence of national sovereignty and the integrity of the state, demanding respect and upholding commitments in the international system. Others identify the domestic attributes of constitutional order and political stability, attained through the formation of a settled framework of government, reliable procedures for leadership succession, and a consolidation of the territorial administrative reach of government institutions. This conspectus owes to the fascination exerted by nation‐building and state‐building in new states of Africa and Asia. It also relates to earlier studies of legal‐rational authority: an endowment of coercive powers and the ability to command obedience. The establishment of bureaucracy, displaying characteristics like division of labor and functional specialization, hierarchy and chain of command, and merit‐based recruitment, is connected.Political development enhances the state's capacity to mobilize and allocate resources, to process policy inputs into implementable outputs. This assists with problem‐solving and adaptation to environmental changes and goal realization. The contemporary notion of good governance also dwells on efficient, effective, and non‐corrupt public administration.